Researching the effects of teaching grammar rules to English second language adult learners - Ayliff, D (South African Journal of Higher Education, 2011)
This article describes the effects of an interventionist form-focused course on the written English of first-year second language university learners. For two semester courses the form (or grammar) of the language was concentrated upon. During the first semester the use of correct grammar was focussed on intensively, while during the second semester the focus on the grammar continued, but less intensively, as the focus shifted also to other aspects of language such as tone, register, style, etc. In particular, various common errors that occur in the written English of second language speakers were targeted during the two semester courses. Pre-, post- and delayed-post-tests showed that there was a significant decrease in the error categories after the intervention and that, while some errors were more resistant to the treatment of these form-focussed courses than others, there was a significant decrease in the error count and that this was sustained in the long-term.